estimation of designs of measurement for the analysis of the violence in televising reporters (Revista Electrónica REDINE, 2018)
In this work designs of measurement by means of a variability analysis were considered  (Analysis of Components of Variance and Analysis of Generalizabilidad) to study the treatment that to him the Venezuelan televising channels grant, to the news on violence. This analysis allowed to consider the reliability, generalizabilidad, and variance associated to each one of the variables of classification in the raised designs of measurement, from two to five facets. For it two observacionales tools were elaborated: a system of field formats and a system of emergent categories.  The results indicate that the considered designs are trustworthy  and generalizables  to populations with characteristics similar to those of the studied sample, in addition adjust to General the Linear Model. Significant differences between the variables Y (intensity of the  news suggested by the televising channel), and Z have been obtained (intensity of the news perceived by the observer). In the variable and (suggested intensity) the models with smaller residual variance, and the greater frequency of meaning were obtained. Of these differences found in the variables, it is possible to be deduced that in the variable "Y ", the television channels could be stimulating the violence, by means of the treatment that they  give  to the  news.
Keywords: violence; the news; variability; designs of measurement